REDEFINING BEAUTY STANDARD IN LAKSMI PAMUNTJAK’S THE QUESTION OF RED - Yulia Eka Pristiana; Much Koiri (PARADIGM: Journal of Language and Literary Studies, 2021)
The word "beautiful" is closely addressed to women. The standardization of beauty attached to women by a patriarchal society has become an issue that is still strongly opposed by feminists. The feeling of being less attractive and less-loved will grow in the women’s minds who are deemed less or do not meet the beauty standard in the patriarchal society. This study is aimed: (1) to discuss beauty standards set forward by a patriarchal society represented through an epic literary work, a novel by Laksmi Pamuntjak entitled The Question of Red, and (2) to identify how the character Amba redefines beauty in Laksmi Pamuntjak's The Question of Red. This study applies literary criticism to achieve satisfactory results, which refers to feminists' "reading as women." This study indicates that patriarchal society's beauty standard is represented by depicting Amba's appearance that is different from the physical depiction of the mother and the sister who always have a beautiful appearance. Besides, Amba believes that the beauty standard is a catastrophe that unwittingly harms women. Moreover, beauty is not always just about appearance.